2011
DOI: 10.1042/bst0390857
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal Aβ as a trigger for neuron loss: can this be translated into human pathology?

Abstract: In the present review, we summarize the current achievements of modelling early intraneuronal Aβ (amyloid β-peptide) accumulation in transgenic mice with the resulting pathological consequences. Of special importance will be to discuss recent developments and the translation of the results to AD (Alzheimer's disease). N-terminally truncated AβpE3 (Aβ starting with pyroglutamate at position 3) represents a major fraction of all Aβ peptides in the brain of AD patients. Recently, we generated a novel mAb (monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…These important biological effects have, not surprisingly, relevant clinical consequences, as indicated by the influence that these gene polymorphisms may exert on the onset and severity of several clinical pathological conditions, including AD [4,5,6,7]. Several studies have suggested that the production, oligomerization and extra- or intraneuronal deposition of β-amyloid peptide, along with intracellular neurofibrillary tangle formation, play central roles in AD [29,30]. Accumulating evidence suggests that inflammation may also play an important role in the initiation or progression of AD [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…These important biological effects have, not surprisingly, relevant clinical consequences, as indicated by the influence that these gene polymorphisms may exert on the onset and severity of several clinical pathological conditions, including AD [4,5,6,7]. Several studies have suggested that the production, oligomerization and extra- or intraneuronal deposition of β-amyloid peptide, along with intracellular neurofibrillary tangle formation, play central roles in AD [29,30]. Accumulating evidence suggests that inflammation may also play an important role in the initiation or progression of AD [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological hallmarks of AD include neurofibrillary tangles consisting of hyper-phosphorylated microtubule-associated protein tau [4,5] and extracellular amyloid plaques derived from amyloid precursor protein (APP), a widely expressed trans-membrane metalloprotein essential for neuronal growth, survival, post-injury and repair [6]. The main component of plaques is amyloid β (Aβ) peptide, (38–43 amino acids) generated by sequential cleavage of APP by β- and γ-secretase [7-10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acting from the extracellular space, where it accumulates in the diseased brain, Aβ also has an intracellular site of action (Wirths et al, 2004). Indeed, as a result of uptake from the extracellular space or via its intracellular synthesis and processing, Aβ has been reported to accumulate within the cell (Pierrot et al, 2004; Bayer and Wirths, 2011; Kaminski Schierle et al, 2011). This intracellular Aβ is also neurotoxic and has been shown to target the ER and the mitochondria, inducing a stress response and causing permeability transition, respectively (Yao et al, 2009; Umeda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%